Does the Porter hypothesis hold in China? Evidence from the low-carbon city pilot policy - Weiping Shen; Yong Wang; Weijie Luo (Journal of Applied Economics, 2021)
Given the constraints of energy, environment, and climate change in the process of economic development, transitioning to a low-carbon economy by such means as the construction of low-carbon cities is a feasible approach to a sustainable development pattern that balances energy conservation, environmental protection, and economic growth. Utilizing the data of listed companies in China A-shares market over the period 2007-2016, we treat China's low-carbon city pilot policy (LCCPP) as a quasi-natural experiment and adopt a difference-in-differences approach to explore the effect of LCCPP on the total factor productivity (TFP) of firms. Firm TFP is found to be negatively associated with the implementation of LCCPP. Our mechanism analysis reveals that the LCCPP stimulates innovation by firms in China, consistent with the weak Porter hypothesis. Moreover, the negative relationship between the LCCPP and TFP holds more strongly in larger firms or those located in the eastern region.
Keywords: L51; O31; Q01; Q54; 330; low-carbon city pilot policy; Porter hypothesis; total factor productivity